2006
DOI: 10.1086/498859
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of the Circumnuclear Radio Supernova SN 2000ft in NGC 7469

Abstract: SN 2000ft is the first radio supernova detected in the circumnuclear starburst of a luminous infrared Seyfert 1 galaxy. It is located at a distance of 600 pc from the QSO-like nucleus of NGC 7469. We report the temporal evolution of SN 2000ft during the 3 years after its discovery. Although SN 2000ft has exploded in the dusty and very dense environment that exists in the nuclear regions of luminous infrared galaxies, it shows the radio evolution properties characteristic of radio supernovae identified as Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 41 publications
3
86
0
Order By: Relevance
“…For example, Ryder et al (2004) inferred the action of a binary companion from periodic modulations in the radio light curve of SN 2000ig, which was subsequently confirmed from imaging at Gemini (Ryder et al 2006). This would make SN 2004ip the second case, only after SN 2000ft in NGC 7469, where such radio monitoring has been carried out for a SN in the circumnuclear starburst of a LIRG and will help to better understand the behavior of SNe within dense starburst environments (e.g., Alberdi et al 2006). Furthermore, Mattila et al (2007b) estimated an average SFR of 135 yr for IRAS Ϫ1 M , 18293Ϫ3413 corresponding to a CCSN rate of ∼1.0 SN per year.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ryder et al (2004) inferred the action of a binary companion from periodic modulations in the radio light curve of SN 2000ig, which was subsequently confirmed from imaging at Gemini (Ryder et al 2006). This would make SN 2004ip the second case, only after SN 2000ft in NGC 7469, where such radio monitoring has been carried out for a SN in the circumnuclear starburst of a LIRG and will help to better understand the behavior of SNe within dense starburst environments (e.g., Alberdi et al 2006). Furthermore, Mattila et al (2007b) estimated an average SFR of 135 yr for IRAS Ϫ1 M , 18293Ϫ3413 corresponding to a CCSN rate of ∼1.0 SN per year.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…An apparent confirmation of such a theory came from the discovery of the radio-bright SN 2000ft (Colina et al 2001a(Colina et al , 2001b) in a circumnuclear starburst ring (∼600 pc from the nucleus) of its LIRG host NGC 7469 ( Mpc). However, the case of SN 2000ft is outstanding D ≈ 70 because its 6 year long VLA monitoring has shown that the supernova shares essentially the same properties that are common to radio SNe identified as Type II SNe, despite having exploded in the dusty and very dense environment of the circumnuclear region (Alberdi et al 2006). We also note that the optical glow of SN 2000ft has recently been identified in archival HST images taken on 2000 May 13 (Colina et al 2007), consistent with the predicted date of the explosion from the analysis of its radio light curves (Alberdi et al 2006).…”
mentioning
confidence: 99%
“…NGC 7469 is a LIRG with L IR = 5 × 10 11 L , at a distance of 70 Mpc (Alberdi et al 2006). NGC 7469 contains a luminous Seyfert 1 nucleus surrounded by a dusty circumnuclear starburst ring of about 1.6 kpc in diameter (Cutri et al 1984;Wilson et al 1986;Wilson et al 1991;Miles et al 1994;Genzel et al 1995;Malkan et al 1998;Scoville et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The new bright source to the west of the nucleus, situated in the well-known cirumnuclear starburst ring, is interpreted as a bright radio supernova [24,25].…”
Section: Pos(8thevn)051mentioning
confidence: 94%
“…Of these sources detected in the centres of dustobscured galaxies, a large fraction are never optically classified. It is assumed that many of them are massive core-collapse supernovae; extreme examples of these sources may be the those found in the centre of Arp220 [5,20,21,22,23] or the luminous radio supernovae detected in NGC7469 [24,25] (see Fig 2).…”
Section: Detections Of Optical and Radio Supernovaementioning
confidence: 99%